A Linear Programming Framework for Cost Allocation and External Acquisition when Reciprocal Services Exist. - Baker, Kenneth R.; Taylor, Robert E. (The Accounting Review, 1979)
ABSTRACT: This paper views the external acquisition of services as a variation of the traditional make-buy problem. A linear programming framework for external acquisition is proposed which generalizes the traditional make-buy model by incorporating the simultaneous equation relationships for reciprocal services. Using linear programming results it is possible to determine whether external acquisitions are economically attractive and in what quantity. In addition, this paper demonstrates how to use the linear programming results to compute cost allocations, even when some overhead services are purchased externally.